Klliopi Logothetis. Interview with Mrs. Heliya Slinko, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA - Logothetis, Kalliopi (Young Scholars Grinchenko – Seton International Journal, 2021)
Kalliopi Logothetis. Interview with Mrs. Heliya Slinko, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA